SOCIO-DEMOGRAPHIC CORRELATES OF JOB SATISFACTION AMONG NURSES AND MIDWIVES IN HEALTH FACILITIES IN THE BOLE DISTRICT OF THE SAVANNAH REGION, GHANA. - Datuah, J. N.; Aninanya, G. A.; Habib, I.; Aryee, P. A. (UDS International Journal of Development, 2022)
In the Ghanaian health system, low job satisfaction has been shown to affect service delivery. It is indicated that poor remuneration, non-conducive working environments and poorly resourced healthcare facilities influence job satisfaction and affect quality healthcare delivery. In this study, the relationship between socio-demographic variables and job satisfaction were examined. An analytical cross-sectional design and a multistage sampling technique were employed and the Mueller/McCloskey Nurse Job Satisfaction Scale was adapted and used to carry out interviews among 156 nurses and midwives in the Bole District of the Savannah Region. Spearman’s correlational analysis was done at 95% confidence level (p<0.05) to establish the association between socio-demographic characteristics and job satisfaction. The study revealed that only few (4.5%) nurses and midwives had a very high job satisfaction level but a majority (78.7%) had a modest level of job satisfaction. Also, an association was established between job type by healthcare profession and job satisfaction (r=0.253, p=0.046<0.05). However, there was no relationship between gender (r=-0.153, p=0.872>0.05); age (r= 0.098, p=0.922> 0.05); marital status (r=-0.120, p=0.137> 0.05); level of education (r=0.055, p=0.576>0.05); working experience (r=0.135, p=0.094) and job satisfaction. Job type by healthcare profession was the only socio-demographic variable that predicted job satisfaction. Whilst the midwives were more likely to be dissatisfied, the nurses were more likely to be satisfied. It is recommended that nursing leaders and policy makers should institute motivational packages in consonance with the job types of these health professionals and respecting their rights to be involved in decision making and creating fair promotion opportunities. Keywords: Nurse, Midwife, Job Satisfaction, Socio-demographic Factors, Bole District.